Prevalence of blighted ovum in first trimester of pregnancy: a hospital based study - A. Mitwally, Abo Bakr; M. Abd El Aal, Diaa Eldeen; Taher, Nermeen; Abbas, Ahmed M. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: The aim of this study is to know the prevalence of blighted ovum among pregnant women in 1st trimester attending our hospital during their antenatal visits and to know the fate of blighted ovum either if there is spontaneous expulsion of the sac or need of medical induction or surgical evacuation. Methods: This observational study was conducted at Obstetrics and Genecology Department, Women Health Hospital and Sahel Selim Hospital, Egypt from November 2015 to February 2018. All patients recruited in this study attended the antenatal care clinics for antenatal follow-up during their first-trimester of pregnancies. Results: All cases of the study were less than 14 weeks. The mean gestational age was 8.93±1.01 (7.0-11.0) weeks. In patients less than 20 years old, (73%) there is a significant increase in surgical treatment (dilatation & curettage) after failure of medical treatment, patients more than 40 years old (50.7%) there is a significant increase in medical treatment after success taking misoprostol so there is no need to a surgical treatment by (dilatation & curettage) in the majority of cases. Conclusions: The prevalence of blighted ovum was 15.6%. Also, the prevalence of blighted ovum was statistically significant increased with increase maternal age and also, we noticed that there was a statistically significant association between early pregnancy failure and a history of previous early pregnancy loss.